Wouldn't it be nice : - Granata, Charles L. (A Cappella Books, 2003)
This illuminating book offers unique insight into the making of the seminal album Pet Sounds, revealing the intimate processes that went into its creation and featuring brand-new interviews with key players. From conception and composition to arrangement and production, the ways in which Pet Sounds changed the face of American popular music are chronicled. While Pet Sounds carries the tag of being a Beach Boys record, this lively exposé reveals just how little input the rest of the band had in its recording ...